Mastering extreme size constraints in the clathrate‐I borosilicide Cs8B8Si38. Issue 2 (22nd January 2021) - Hübner, Julia‐Maria; Jung, Walter; Koželj, Primož; Bobnar, Matej; Cardoso‐Gil, Raul; Burkhardt, Ulrich; Böhme, Bodo; Baitinger, Michael; Schwarz, Ulrich; Grin, Yuri
Abstract: Cs8 B8 Si38 is obtained by high‐pressure high‐temperature synthesis at p =8 GPa and T =1273 K. The new compound (space group Pm 3 ‾ n ; a =10.0312(3) Å) is the third example for a clathrate‐I borosilicide after the potassium and rubidium varieties, respectively. The phase slowly deteriorates in air and moisture but is thermally stable up to 1050 K at ambient pressure. [Cs + ]8 [B – ]8 [Si 0 ]38 is electronically balanced, diamagnetic, and shows semiconducting behavior. Abstract :